A Comparative Study of the Preferential Principle of "Prioritizing Qurʾānic Verses Over Opposing Opinions" in the Views of ʿAllāmah Ṭabāṭabāʾī and Ibn ʿĀshūr - Seyyedeh Masumeh Fatemi; Mahdi Hemmatiyan (آموزه‌های قرآنی, 2024)
Preferential exegetical principles constitute rigorous methodological frameworks enabling an exegete to ascertain the most authoritative interpretation among competing hermeneutical perspectives. One such principle, frequently invoked within the exegetical tradition, is the rule of “Prioritizing Qurʾānic Verses Over Contradictory Opinions.” According to this principle, the exegete privileges an interpretation consonant with the apparent signification of other thematically affiliated verses over hermeneutical positions that diverge from or contradict this coherence. This study undertakes a comparative-exegetical inquiry into the application of this principle by two of the most eminent contemporaneous exegetes of the Shīʿī and Sunnī traditions, ʿAllāmah Ṭabāṭabāʾī and Ibn ʿĀshūr, with particular focus on their interpretations of the Qurʾānic verses concerning the encounter of transgressors with the angels (al-Furqān, 25:22) and intercession (al-Baqarah, 2:48). Adopting a descriptive-analytical approach, this research scrutinizes the extent to which these exegetes have engaged with and operationalized the preferential principle in their respective commentarial methodologies. The findings demonstrate that ʿAllāmah Ṭabāṭabāʾī systematically applies this principle in his hermeneutical deliberations on the aforementioned verses. By meticulously analyzing the syntagmatic and paradigmatic structures of Qurʾānic discourse, he construes yawm (Arabic: الیوم, lit: the day) in al-Furqān 25:22 as denoting the moment of death, thereby unequivocally repudiating alternative exegeses that depart from this reading. Conversely, Ibn ʿĀshūr exhibits an apparent disregard for the preferential principle in his exegesis of this verse, thereby incorporating and validating opposing interpretative positions. However, concerning al-Baqarah 2:48, both exegetes acknowledge the principle’s validity and affirm the plausibility of intercession contingent upon divine sanction, though ʿAllāmah Ṭabāṭabāʾī’s argumentation is considerably more robust and hermeneutically substantiated than that of Ibn ʿĀshūr.